Multifaceted aspects of chronic disease: do diffuse idiopathic skeletal hyperostosis affect the quality of life? - Greta Pellegrino; Valeria Giorgi; Piercarlo Sarzi-Puttini (Exploration of Musculoskeletal Diseases)
Diffuse idiopathic skeletal hyperostosis (DISH) is a common condition that affects the spine and peripheral joints, characterized by the progressive ossification of ligaments and tendons. It is a non-inflammatory degenerative disease that affects predominantly the elderly population. It has been associated with reduced mobility and chronic pain, which can have a significant impact on patients’ quality of life (QOL). Although DISH has always been considered a benign condition, patients with DISH report higher levels of pain, stiffness, and disability compared to the general population. It can affect their ability to perform daily activities and participate in social and recreational activities. In addition, extra-spinal manifestations such as enthesopathy and involvement of peripheral joints, but still dysphagia and airway obstruction have been described in DISH. These, although not as common, when present result in signs and symptoms significantly impacting the patient’s QOL. The objective of this review is to assess the QOL in individual with DISH. This involves an examination of various facets of the condition, including pain, spinal and extraspinal manifestations, fractures, and metabolic syndrome.